Influence of the solar energy on the self-organization of water molecules. Diurnal, annual, and 11-year variations - Shevchenko, I.V. (Доповіді НАН України, 2019)
Solar energy exerts a strong influence on the ability of water molecules to the self-organization. This influence is manifested on the chemical reactivity of water clusters. The rate of hydrolytic reactions involving water clusters can vary within very large limits over the course of minutes, hours, days, months, and years. The results of regular 4-year (2015-2018) investigations of the hydrolysis of triethylphosphite in acetonitrile indicate that the rate of this reaction with all other conditions being equal displays diurnal and annual variations and may be also modulated by the 11-year cycles of solar activity. The hydrolytic cleavage of a phosphorus-oxygen bond in triethylphosphite can be considered as a simplified model system of the conversion of adenosine triphosphate (ATP) to adenosine di phosphate (ADP), which is known to underlie bioenergetics processes in living organisms. The dependence of biochemical processes on the solar activity during the rotation of the Earth around its axis and around the Sun is well known in all forms of life (in plants, animals, fungi, and bacteria) as circadian and circannual rhythms. For example, owing to the 11-year cycles of solar activity, the annual growth rings in trees have different thicknesses and are arran ged in 11-year sequences. Taking into account that water is a necessary constituent in all forms of life, one can suppose that the discovered diurnal and annual variations of the water reactivity may underlie the circadian and circannual rhythms.